I Internalisasi Budaya Malaqbiq Dalam Akuntabilitas Pengelolaan Dana Desa : Internalisasi Budaya Malaqbiq Dalam Akuntabilitas Pengelolaan Dana Desa - Risma Eka Saputri; Abd Wahab; Jamaluddin Majid (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This study aims to assess the accountability of village fund financial management through the cultural values of malaqbiq in Mekkatta village, Majene Regency. This research is a qualitative research with ethnographic method. The source of this research data is through direct interviews with several respondents who come from the research area. The results showed that the accountability system for the financial management of the Mekkatta Village Fund was not in accordance with the standards and principles of accountability, where the management of the APBDes by village officials was less transparent to the community. This shows that the cultural values of malabiq are related to honesty and responsibility, the cultural values of malaqbiq kedo and gauq (honesty) and malaqbiq pau (honest) in being responsible for an act to Allah SWT, but the presence of the Malabiq culture has not been able to increase accountability for the financial management of Mekkata village funds